Cover Feature: Photoanodes for Aqueous Solar Cells: Exploring Additives and Formulations Starting from a Commercial TiO2 Paste (ChemSusChem 24/2020). Issue 24 (24th November 2020) - Fagiolari, Lucia; Bonomo, Matteo; Cognetti, Alessio; Meligrana, Giuseppina; Gerbaldi, Claudio; Barolo, Claudia; Bella, Federico
Abstract : The Cover Feature shows a modern building powered by aqueous solar cells, placed both indoors and outdoors. Transparency, colors, and safety: new ingredients for hybrid photovoltaics. The cover is designed by Barth van Rossum. More information can be found in the Full Paper by L. Fagiolari et al .